Relationship among Periodontal Disease, Apical Periodontitis and Offspring Health - Mattera, Maria Sara de Lima Coutinho; Tsosura, Thaís Verônica Saori; Pereira, Renato Felipe; Chiba, Fernando Yamamoto; Marani, Fernando; Belardi, Bianca Elvira; Tessarin, Gestter Willian Lattari; Santos, Rodrigo Martins dos; Matsushita, Doris Hissako (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The relationship between maternal health and the fetal environment has been widely discussed in recent decades. Several studies have shown that insults that occur during the perinatal period modify fetal development, leading to harmful long-term results that culminate in pathologies in adulthood. Periodontal diseases (PD) comprise a wide range of inflammatory conditions that affect the supporting structures of the teeth (the gingiva, bone and periodontal ligament). Apical periodontitis (AP) is an inflammation at the apex of the thoot root usually caused by infection by bacteria from the root canal system. The present study aims to show the effects of maternal oral inflammations on the offspring health. The study provides information that both, maternal PD and AP, have negative effects in the short and long-term on the offspring health. Thus, adequate oral health can prevent adverse pregnancy outcomes and permanent changes in adult offspring. That is, oral hygiene during pregnancy should be encouraged.